Understanding mediators and moderators of the effect of customer satisfaction on loyalty - Lovemore Chikazhe; Charles Makanyeza; Blessing Chigunhah (Cogent Business & Management, 2021)
Customer satisfaction, loyalty and corporate image play a critical role in improving loyalty within the banking sector. The current study examines the mediators and moderators of the effect of customer satisfaction on loyalty. Data were collected from bank customers (n = 308) using a structured questionnaire through a cross-sectional survey in Chinhoyi, Zimbabwe. Data were analysed using structural equation modelling and moderated regression analyses. Customer satisfaction has a direct positive effect on customer loyalty. Service quality and corporate image were each found to partially mediate the effect of customer satisfaction on customer loyalty. Gender, age, education and income were found not to moderate the effect of customer satisfaction on loyalty. Thus, this study extends the extant services marketing literature by examining the mediators and moderators of the customer satisfaction-customer loyalty relationship within the banking sector. As a result, banks are encouraged to consider customer satisfaction, service quality and image altogether when trying to influence customer loyalty.
Keywords: 650; corporate image; customer loyalty; customer satisfaction; perceived service quality; Zimbabwe